Comparison of the effects of various supporting electrolytes on the treatment of a dye solution by electrocoagulation process - Keyikoğlu, Ramazan; Can, Orhan Taner; Aygün, Ahmet; Tek, Ahu (Elsevier, 2019)
Laboratory experiments were conducted to investigate the effect of some supporting electrolytes on the treatment of Reactive Black 5 (RB5) by electrocoagulation using aluminum and iron electrode couples. Electrolytes, which contain Cl-, SO42-, NO- anions and Na+, K+, NH4+ cations, were compared in terms of color removal efficiencies. The presence of SO42- led to poor performances with aluminum electrodes yielding a removal efficiency close to 45% at 8.33 A/m(2). Similarly, the presence of NO3- when iron electrodes were used adversely affected the process performance. The removal efficiency with KNO3 was 49.1% at 8.33 A/m(2). Overall Cl- containing electrolytes performed well achieving almost complete decolorization (99.9%) regardless of the electrode type. The performance of Al electrode considerably improved in the presence of NH4+, achieving 98.0% and 99.1% removal efficiencies at the current densities of 4.17 A/m(2) and 8.33 A/m(2), respectively in 10 min treatment duration.
Keywords: Supporting electrolytes; Electrocoagulation; Dye removal; Reactive black 5